Proses Produksi Iklan Digital Top Genzation Oleh Prambors Radio untuk Menarik Pengiklan - Kharamain, Muhammad Mizanul; Parlindungan, Davis Roganda (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
In the current era of digitalization, producing compelling advertisements requires precise creativity to capture advertisers’ attention. This study aims to analyze and describe the digital advertising production process employed by Prambors Radio Jakarta in attracting advertisers. Adopting a post-positivist paradigm and a qualitative approach, the research identifies three key stages in the production of the Top Genzation digital advertisement. The pre-production stage involves developing an editorial plan encompassing the advertising concept and distribution strategy. The production stage engages graphic designers and editors to craft visually appealing digital advertisements. The post-production stage includes delivering performance reports and traffic data to advertisers as a measure of advertising effectiveness. The study concludes that by systematically implementing these stages, Prambors produces creative, high-quality, and well-targeted digital advertisements that effectively enhance advertiser engagement.